Ok so,
Simplifying
4x + 4y + 4z + 4 = 0
Reorder the terms:
4 + 4x + 4y + 4z = 0
Solving
4 + 4x + 4y + 4z = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + 4x + 4y + -4 + 4z = 0 + -4
Reorder the terms:
4 + -4 + 4x + 4y + 4z = 0 + -4
Combine like terms: 4 + -4 = 0
0 + 4x + 4y + 4z = 0 + -4
4x + 4y + 4z = 0 + -4
Combine like terms: 0 + -4 = -4
4x + 4y + 4z = -4
Add '-4y' to each side of the equation.
4x + 4y + -4y + 4z = -4 + -4y
Combine like terms: 4y + -4y = 0
4x + 0 + 4z = -4 + -4y
4x + 4z = -4 + -4y
Add '-4z' to each side of the equation.
4x + 4z + -4z = -4 + -4y + -4z
Combine like terms: 4z + -4z = 0
4x + 0 = -4 + -4y + -4z
4x = -4 + -4y + -4z
Divide each side by '4'.
x = -1 + -1y + -1z
Simplifying
x = -1 + -1y + -1z